An overview of categories of identity in the late xix – early xx centuries on the territory of modern uzbekistan (Journal of history, 2019)
Abstract. Аt the moment, the process of formation and development of the Uzbek identity is one of the key issues in the ethnology and anthropology of Uzbekistan. Today, the historical, ethnologicaland anthropological science of Uzbekistan is on the verge of a new stage of development. With independence, the development of historical science did not occur uniformly. The long existence under thecontrol of the Soviet government also influenced the scientific activities of each state. Basically, the scientific traditions of the twentieth century and the methodology almost invariably continued to existafter the creation of independent states of Central Asia. The set course by Soviet scientists continued and still continues to have an impact on the worldview of the local intelligentsia. When in the Westand in Russia itself already from the end of the twentieth century, a revision of the old paradigms and their rethinking, the creation of new directions, such as constructivism, ethnosymbolism, modernismand postmodernism, began in Uzbekistan still continue to study historical sciences in accordance with Soviet theories of statehood. Local researchers, instead of researching and studying new and new theories,continue to rewrite and retell old ones. As a result, a large gap has appeared between the studies of foreign experts and local ones. Several key factors, such as: lack of knowledge of a foreign language,limited access to foreign sources, a scanty amount of joint research, and others eventually led to stagnation in this direction. The purpose of this article is to study and analyze English-language materials onthe identity of Uzbeks before the colonial period. Also, in the article we will try to show what categories of identities existed in Central Asia, in particular in the territory of modern Uzbekistan and to reveal howmuch this stage of the history of Uzbeks was consecrated in foreign literature. The study of this period is relevant in that, without knowledge and understanding of existing identities before the formation of theUzbek identity, we will not be able to fully see the picture of this process. As a result, we will be able to understand what identities the Uzbek national identity has united. At the end of the article, we willidentify the main barriers that have become the reason for the study of this question and try to give our recommendations to fill the existing gaps.